Immunogenicity of Sputnik V, BBIBP-CorV and ChAdOx-1S vaccines in naïve and previously infected individuals from Tandil, Argentina - Gutiérrez, Silvina Elena (2022)
Mass vaccination has been the key element in controlling the COVID-19 pandemic. Vaccination in Tandil began in January 2021 for health care workers, which mainly received Sputnik V (SpV). The inactivated vaccine from Sinopharm (Si) and the ChAdOs-1S vaccine from AstraZeneca (AZ) were available since March 2021. We aimed to measure and compare anti-SARS CoV-2 spike (S) antibodies in naïve and seropositive individuals after receiving first and second dose of different vaccines.A total of 141 individuals were recruited between January and August 2021. Serum samples were obtained before vaccination and after each vaccine dose. Specific anti-S antibodies were quantified using the COVIDAR IgG ELISA. Results were log transformed and a repeated measures ANOVA was adjusted. Seventy one of the individuals had detectable anti-S antibodies due to previous infection while 70 were seronegative before receiving the first dose (initial status). Fifty four from 71 (76%) of the initially seronegative participants seroconverted after the first dose. All but one of the non-seroconverters received the Si vaccine. After the second dose 95.8% of the participants seroconverted. Differences were observed depending on the initial status, type of vaccine and number of doses received (p= 0.0017). The titer of antibodies elicited against the 1° dose was influenced by the initial status of the individual for the 3 vaccines. After the vaccination scheme was completed, there were also differences in the level of specific antibodies achieved depending on the initial status in those who received the Adenovirus vectored vaccines. Both in naïve and sensitized participants SpV and AZ induced higher levels of antibodies compared to Si (p> 0.05). Sinopharm resulted the less immunogenic vaccine. This result may be due to the interval between shots, which was 47 days mean, instead of the recommended 21-30 days. Therefore, individual with 2 doses of Si may be benefited with heterologous booster.